Gender Differences in Maltese Ballad Singing - Erler, Annette (Danish Yearbook of Musicology, 1999)
Gender Differences in Maltese Ballad Singing Diversity in social contexts and performance practices is investigated in the ballad singing tradition on the Mediterranean islands of Malta and Gozo. The vocal genre is analysed on the basis of recordings from the late 1980s and exemplified in this article by three representative musical transcriptions. Ballad singing is gendered female or male and the two are distinguished by the terminology. Ballad singing among female singers is usually called poezija, while male singers call it tal-fatt. The musical practice of both sexes is the same insofar as they use the same pitch compass for singing, but the two differ in the use of dynamic levels, pronunciation, and recently the melodic material too. Whether there is instrumental accompaniment depends on the singer’s sex too, since female singing is solo and male singers are accompanied by the guitar. The accompaniment affects the mode of singing in terms of much stronger adherence to key and metre. Other social differences affect ballad performance practices, since sex segregation establishes the opportunities for ballad tradition and textual preferences condition the function of ballad singing. The traditional contexts and styles are associated with old-fashioned ideas and are less valued than contemporary staged performances. The latter involve men only and incorporate new influences. Ballad singing is therefore becoming a formalised kind of male performance for the public since traditional ballad singing is falling into disuse and has almost disappeared. The tradition of ballad singing on the Maltese islands indicates how social differences affect practice, resulting in distinct musical practices.